The Multiple Facilitator: Scientists, Sages and Rascals. (June 2021) - Jansen, Rob J. G.; van Zelst, Marino
Background: Games are designed to help participants think about, understand, sharpen their problem statement as well as the specific objectives to be achieved to escape the problem situation. When participants prepare for the game (briefing), interact in the simulated environment (gameplay), and self- or jointly reflect about the gameplay they faced in terms of intended and unintended learning experiences (debrief), they benefit or suffer fromfacilitating that can or cannot fully cater to their needs. To support the participants to explore and resolve the problem situation in order to achieve learning goals, we propose that facilitators can make use ofrole shifts during gameplay. Method: To capture therole shifts in the gameplay phase we studied game runs of the MicroTech game. The MicroTech game is afree-form game in which participants play the role of top management team or division managers in a multiunit organization. Results: We analyzed therole shifts we experienced as facilitators by elaborating on game events and how we could manage those events differently in future game runs if necessary. We show a need for facilitators to be able to embody multiple roles in the case of policy gaming that are in fit with the different phases, while there is a simultaneous need to shift within phases in order to keep participants moving and stimulating them to work towards the learning goals. Conclusion: Gaming/simulation facilitators should explore what multiplicity is required of them to make the game a success. Although this may seem normal practice to well-prepared and professionally trained facilitators, this may be particularly important for novice facilitators.